Temperature-Modulated Expression of Allometric Respiration Strategies Supports a Metabolic Scaling Rule - Rakocinski, Chet F.; Gillam, Kelsey Burns (Frontiers in Marine Science, 2017)
A model based on the mass-specific oxygen consumption rate of the tolerant polychaete, Capitella telata, related meaningfully to a novel metabolic scaling rule as applied to the infaunal size spectrum. Depending on temperature, C. telata expressed divergent oxyregulating or oxyconforming strategies relative to oxygen availability. A non-linear response surface fitted to the allometric exponents of a family of VO2 curves for 12 treatment combinations of DO saturation and temperature was used to project oxygen consumption rates across the infaunal size spectrum. Plasticity in respiration strategies was evident, based on four simulated dynamic 32 d oxygen-temperature exposure scenarios and on simulated static oxygen-temperature exposures. The oxyconforming strategy of C. telata expressed under hypoxia near the upper thermal limit agreed with a hypothesized allometric scaling rule based on metabolic ecology. Conversely, an oxyregulating respiration strategy was expressed at cooler temperatures under low oxygen concentration, except organisms hyper-regulated relative to normoxic conditions. At warm temperatures, small organisms exhibited relatively greater metabolic depression than large organisms; whereas at cool temperatures, small organisms hyper-regulated relatively more than large organisms. Dichotomous shifts in respiration strategies likely reflect a breakdown in the functioning of special adaptations, and reliance on alternative coping mechanisms. Divergent temperature-dependent respiration strategies illustrate how responses to multiple stressors can be synergistic. Moreover, results imply that population responses to hypoxia may differ, depending on prevailing temperature regimes.